Assessment of the flexural strength of two heat-curing acrylic resins for artificial eyes - Fernandes, Aline Úrsula Rocha [UNESP] (2009)
Prosthetic eyes are artificial substitutes for the eyeball, made of heat-curing acrylic resin, serving to improve the esthetic appearance of the mutilated patient and his/her inclusion in society. The aim of this study was to assess the flexural strength of two heat-curing acrylic resins used for manufacturing prosthetic eyes. Thirty-six specimens measuring 64 x 10 x 3.3 mm were obtained and divided into four groups: acrylic resin for artificial sclera N1 (Artigos Odontológicos Clássico, São Paulo, SP, Brazil), heat-cure water technique (GI) and microwave-cured (GII); colorless acrylic resin for prosthetic eyes (Artigos Odontológicos Clássico, São Paulo, SP, Brazil), heat-cure water technique (GIII) and microwave-cured (GIV). Mechanical tests using three point loads were performed in a test machine (EMIC, São José dos Pinhais, PR, Brazil). The analysis of variance and the Tukey test were used to identify significant differences (p < 0.01). Groups GII and GIV presented, respectively, the highest (98.70 ± 11.90 MPa) and lowest means (71.07 ± 8.93 MPa), with a statistically significant difference. The cure method used for the prosthetic eye resins did not interfere in their flexural strength. It was concluded that all the resins assessed presented sufficient flexural strength values to be recommended for the manufacture of prosthetic eyes.